Effectiveness of Group Cognitive Behavior Therapy to Reduce Academic Procrastination Behavior of High School Students During Distance Learning - Mutmainnah, Mutmainnah; Djuwita, Efriyani (Faculty of Psychology, Universitas Negeri Yogyakarta, 2021)
The policy of implementing Distance Learning in Indonesia during the COVID-19 pandemic brought changes to students' academic activities. Such condition may pose a risk that leads to academic procrastination, especially for boys at the high school level (SMA), a group that has been previously known to be prone to academic procrastination behavior. This study aims to determine the effectiveness of Group Cognitive Behavior Therapy (CBT) approach to reduce academic procrastination and develop adaptive strategies for young person. The participants of this study were 4 high school students, male, and aged 16-17 years who were recruited online through purposive sampling technique. Changes in the level of academic procrastination were measured based on the decrease in the irrational procrastination scale (IPS) scores during pre-test, post-test, and follow-up as well as qualitative results obtained based on interviews and observations of participants. The results of the intervention showed that there was a decrease in the participants' academic procrastination scores. Participants also reported that there were positive changes they felt after following the intervention.